2000년대 초에 유행한 Orientia tsutsugamushi에 의한 간염 - 박재일; Park Jae Il; 한성희; Han Seong Hui; 조승철; Jo Seung Cheol; 조용현; Jo Yong Hyeon; 홍상모; Hong Sang Mo; 이학현; Lee Hag Hyeon; et al. (Clinical and molecular hepatology, 2003)
목적: Orientia tustsugamushi 감염은 삼림에 서식하는 매개충인 진드기(Leptotrombidium)의 유충이 우연히 사람의 피부를 통하여 전파되어 생기는 급성 발열 질환이다. 저자들은 지난 3년 동안 쯔쯔가무시병으로 진단된 환자들에서 간 기능 이상을 확인하고 가을철 간염환자의 감별진단 특히 non-A, non-B, non-C 간염의 진단에 주의를 환기하고자 관찰 결과를 보고하는 바이다. 대상과 방법: 한양대학교 서울병원과 구리병원에 2000년 10월부터 2002년 11월까지 hemagglutinin 법으로 쯔쯔가무시병으로 진단된 환자 22명을 조사 대상으로 삼아 그 진료기록을 조사하였다. 결과: 남년 비는 1:3.4로 여자가 많았다. 연령(범위 31-83세)은 56.4±2.6(평균±표준오차)세였다. 입원시기는 9월 23일부터 11월 15일 사이였고 10월 중순 이후 11월 상순 사이가 제일 많았다. 증상은 발열이 21예로 가장 많았고 근육통 13예, 관절통 12예, 오한 6예, 피부발진 6예 순이었다. 잠복기는 7-9일이 10예로 가장 많았고 13-15일이 4예, 10-12일 3예, 3일 이내 3예, 4-6일 2예였다. ALT(범위 18-345 IU/L)는 93.2±17.3 IU/L(평균±표준오차)였고, AST(범위34-255 IU/L)는 92.5±11.7 IU/L, GGTP (범위 19-251 IU/L)는 132.2±14.5 IU/L로 상승하였지만 혈중 총 빌리루빈은 정상이었다. 모든 환자들은 doxycycline 투여로 호전되었다. 결론: Orientia tsutsugamushi 감염은 대부분, 경도의 간 기능 이상을 동반하므로 특히 가을철 간 기능 이상을 보이는 열성 질환 환자에게서 다른 간 질환과 감별해야 할 질환으로 인지하는 것이 중요하다. Background/Aims: Orientia -tsutsugamushi infection is an acute febrile due to the accidental transmission through human skin of forest dwelling vector Leptotrombidium larva. The authors observed liver dysfunctions in patients diagnosed with tsutsugamushi disease (Scrub typhus) in the past 3 years and report the data in the hope of bringing attention to this disease in the differential diagnosis of autumn-season hepatitis, especially of non-A, non-B and non-C hepatitis. Methods: Medical records of 22 patients diagnosed with tsutsugamushi disease by the hemagglutinin method between October 2000 and November 2002 were reviewed. Results: Female gender was dominant in the ratio of 3.4:1. Mean age was 56.4±2.6. Admission was between 23rd September and 15th November with the peak between mid October and early November, Fever, being the most common symptom, was observed in 21 cases, myalgia in 13, arthralgia in 12, chills in 6, and skin rash in 6. An incubation period of 7-9 days was most common (10 cases), 13-15 days (4), 10-l2 days (3), within 3 days (3), and 4-6 days (2), Average ALT, AST and GGTP were increased to 93.2±17.3 IU/L (18±345 IU/L), 92.5±l1.7 IU/L (34-255 IU/L) and 132.2±14.5 IU/L (19-251 IU/L), respectively, but total bilirubin was normal. All the patients improved with doxycycline therapy. Conclusions: Since it usually shows liver dysfunction, it is important to take Orientia tsutsugamushi into consideration in differential diagnosis of autumn-season, febrile hepatic disease.(Korean J Hepatol 2003;9:198-204)